THE ROLE OF SCHOOL PRINCIPALS IN TEACHER WORK ACHIEVEMENT THROUGH THE PHYSICAL WORK ENVIRONMENT AND DISCIPLINE (EMPIRICAL STUDY OF CILEGON CITY ELEMENTARY SCHOOL TEACHERS) - Lithasari, Agustine; Lumangkun, Jimi; Muslimah, Muslimah; Ilham Maliki, Budi (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2024)
Work performance is a result obtained by an employee in carrying out the tasks assigned to him. The study aims to optimize the mediating role of the physical work environment and discipline between the school principal's role and teacher work performance. The type of research method is quantitative, using a survey method to collect respondent data via Google Form from elementary school teachers and analyze it using statistical structural equation modeling (SEM) tools to test direct and indirect influences on variables. According to the study's findings, 1) the principal's position affects the physical work environment, and 2) the principal's function has no impact on discipline. 3) The physical workspace has an impact on how well teachers execute their duties. 4) The effectiveness of teachers' work is unaffected by discipline. In conclusion, work performance is influenced by the physical environment, which is supported by the role of the school principal in enforcing discipline.